The Ḫa–BI–ru. Kin or Foe of Israel? III - Kline, M. G. (1957)
Ḫa–BI–ru–Hebrew Relations: The Usage of ‛Ibrîm in the Old Testament [‛Ebed ‛Ibrî Legislation; ‛Ibrîm in I Sam. 13-14; Abraham the ‛Ibrî Conclusion]; Phonetic Relation of Ḫa-BI-ru to ‛Ibrî; Amarna Age Encounter.